The analysis of dynamic phenomena in technological system at milling case details - Katruk, O. (НТУ "ХПИ", 2018)
This article is intended to analyze the dynamic phenomena origin reasons in the process of milling as oscillatory cutting process and multimass elastically dissipative systems of the machine, reveal the origin conditions of pre-resonant and resonant phenomena in the system, and their mechanism and the energy level of performance and impact on the dynamic stability of the processing system.
Keywords: resonant phenomena; milling thin-walled parts; cutting force; technological processing system; phase-frequency characteristics